Everyday religion : an archaeology of protestant belief and practice in the nineteenth century - Kruczek-Aaron, Hadley (Gainesville : University Press of Florida, 2015)
This book will employ historical archaeological evidence to broadly examine the forces that fed the Second Great Awakening and how a range of communities responded to the activist religious fervor of the time.
Archaeology and everyday religion: an introduction -- The second great awakening and the remaking of everyday life -- Archaeology and the second great awakening -- Awake in the burned-over district -- Perfecting the home front -- Community response to reform's alarm -- Struggling over religion and reform in the past and the present -- Remembering everyday religion: conclusions.
Includes bibliographical references and index.
Print version record.
English.
Master record variable field(s) change: 072
Keywords: Second Great Awakening -- United States; Protestantism -- United States -- History -- 19th century; Christian sociology -- United States -- History; Revivals -- United States -- History; United States -- Church history -- 19th century; RELIGION -- Christianity -- History; Christian sociology; Protestantism; Revivals; Second Great Awakening; United States; SOCIAL SCIENCE / Archaeology; 1800-1899; Electronic books; Church history; History